PENINGKATAN HASIL BELAJAR SISWA DALAM PEMBELAJARAN PENDIDIKAN KEWARGANEGARAAN MENGGUNAKAN MODEL KOOPERATIF TIPE TALKING STICK - Misnawati, Misnawati; Asran, Mastar; Margiati, Margiati (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
The purpose of this study is to improve the ability of teachers in planning, implementing learning, and student learning outcomes in learning Citizenship Education by using cooperative type of talking stick model in class V SD Negeri 14 Pontianak Selatan. This research uses descriptive method with research form that is class action and is collaborative. Subjects in this study were teachers, collaborators, and grade V students, amounting to 35 students consisting of 16 men and 19 women. The technique used is direct observation technique and document scrutiny technique with data collecting tool that is observation sheet and document observation sheet. Data presentation techniques are tables and data analysis to find the teacher ability score in planning and implementing learning and improvement of learning outcomes of Citizenship Education. The results of the study were as follows: (1) the ability of the teacher to plan the learning in the first cycle of meeting I was 2.96, the first cycle of meeting II was 3.70, while the second cycle of meeting I was 3.72, the second cycle of meeting II was 3.87 ( 2) the ability of teachers in implementing learning in the first cycle of meeting I is 2.74, cycle I meeting II is 3.52, while cycle II of meeting I is 3.70, cycle II meeting II is 3.85. (3) The result of study at cycle I meeting I is 64,29, cycle I meeting II is 71,76 whereas cycle II meeting I is 76,67, cycle II meeting II is 83,08. Thus, it can be concluded that there is an increase in the ability of teachers in planning, implementing, and learning outcomes of students in learning Citizenship Education by using the model of cooperative type talking Stick.Â Keywords: Improved, type of talking stick model,learning outcomes, civic education learning.